SIMULASI ALIRAN PASIEN RAWAT INAP UNTUK MENGURANGI BOTTLENECK - Thomas Sonny Soegiharto; Anna Maria Sri Asih (Universitas Gadjah Mada, 2015)
Bottleneck is possible to occur in a system like hospital, especially in admission and discharge of inpatient processes. It can have impact on increasing waiting time and delayed time. Some alternatives were proposed to reduce them, i.e. shift scheduling and human resource allocation. This research modelled real system accompanied by two scenarios: the first scenario was conducted by balancing human resource utility without altering number of employees, whereas the second scenario considered possibility of changing number of employees. The results showed that both scenarios produced reduction of waiting time and delayed time. The first scenario is more feasible compared to the second as no hiring or firing employees occurred, resulting in waiting time reduction of 110.6 minutes (15%) and decrease in delayed time by 184 minutes (15.9%). The reduction of waiting time and delayed time is higher in scenario 2, which are 423.6 minutes (57%) and 281 minutes (24%), respectively. However, there must be 4 additional employees hired in pharmacy applied in scenario 2.